ANALISIS HUBUNGAN PROFITABILITAS TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL - Marisanti Marisanti; Endang Kiswara (Diponegoro Journal of Accounting, 2012)
The purpose of this study was to examine the relationship between the profitability with the level of Intellectual Capital Disclosure on banking industry in Indonesia. The profitability is measured using the ratio of Earnings Before Interest, Taxes, Depreciation and Amortization (EBITDA) and net income to its total assets, and the level of Intellectual Capital Disclosure (ICD) is measured using Intellectual Capital Disclosure Index. The population on this study was a banking industry listed in Indonesia Stock Exchange (IDX) for the year 2010 and 2011. The research sample is 54 companies. Type of data used is secondary. Analysis tool used was pearson correlation. The analysis data technique and hypothesis testing using SPSS software. The result of this research supported a statistically significant inverse relationship between the level of intellectual capital disclosure with EBITDA and net income. The simultaneous analysis resulted that both EBITDA and net income affect the level of intellectual capital disclosure but not inferential for all populations sampled research.